The Role of microRNAs in Helicobacter pylori Pathogenesis and Gastric Carcinogenesis - Noto, Jennifer M.; Peek, Richard M. (Frontiers in Cellular and Infection Microbiology, 2012)
Gastric carcinogenesis is a multistep process orchestrated by aberrancies in the genetic and epigenetic regulation of oncogenes and tumor suppressor genes. Chronic infection with Helicobacter pylori is the strongest known risk factor for the development of gastric cancer. H. pylori expresses a spectrum of virulence factors that dysregulate host intracellular signaling pathways that lower the threshold for neoplastic transformation. In addition to bacterial determinants, numerous host and environmental factors increase the risk of gastric carcinogenesis. Recent discoveries have shed new light on the involvement of microRNAs (miRNAs) in gastric carcinogenesis. miRNAs represent an abundant class of small, noncoding RNAs involved in global post-transcriptional regulation and, consequently, play an integral role at multiple steps in carcinogenesis, including cell cycle progression, proliferation, apoptosis, invasion, and metastasis. Expression levels of miRNAs are frequently altered in malignancies, where they function as either oncogenic miRNAs or tumor suppressor miRNAs. This review focuses on miRNAs dysregulated by H. pylori and potential etiologic roles they play in H. pylori-mediated gastric carcinogenesis.